1997
DOI: 10.1063/1.474002
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity calculations of n -alkanes by equilibrium molecular dynamics

Abstract: We report shear viscosity results obtained using extensive equilibrium molecular dynamics simulations. By direct numerical comparison, we show the equivalence of the Green-Kubo and Einstein approach to the calculation of viscosity in both the atomic and molecular representations. Comparing the results for two models of linear alkanes, we discuss the molecular factors determining their low-temperature liquid-state transport properties. In the mass range considered here (⩽C16), large corrections to Rouse-dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
216
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(249 citation statements)
references
References 33 publications
26
216
3
Order By: Relevance
“…Using this method, Mondello et al showed that 0 of medium long chains may be estimated from the longest relaxation time measured in EMD simulations by invoking the Rouse model. 5,6 They found that the estimates are in good agreement with extrapolated NEMD results ͑within 20%͒. Moore et al have performed NEMD simulations of a C 100 melt ͑close to our C 120 ͒ at various shear rates.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Using this method, Mondello et al showed that 0 of medium long chains may be estimated from the longest relaxation time measured in EMD simulations by invoking the Rouse model. 5,6 They found that the estimates are in good agreement with extrapolated NEMD results ͑within 20%͒. Moore et al have performed NEMD simulations of a C 100 melt ͑close to our C 120 ͒ at various shear rates.…”
Section: Introductionsupporting
confidence: 53%
“…24 Several simulation studies have shown this to be correct. 5,11 The difference between the viscosity calculated from the molecular tensor and that from the atomic tensor is found to converge to zero much faster than the longest relaxation time of the molecule. This was confirmed in test runs of our system in which we calculated the shear relaxation modulus from both atomic and molecular stress tensors.…”
Section: ͑11͒mentioning
confidence: 99%
See 2 more Smart Citations
“…One should notice that at the particular state point of 423.15 K and 1 MPa, which corresponds to the lowest density considered, all models examined showed the least accurate behavior. Earlier studies for pure n-alkanes by Mondello et al [62][63][64] have shown overestimation of self-diffusion coefficients by UA force fields.…”
Section: Diffusion Coefficient and Viscosity Calculations The Diffusmentioning
confidence: 99%